Multilayers of zinc-blende half-metals with semiconductors - P. Mavropoulos; Galanakis, I.; P.H. Dederichs (JOURNAL OF PHYSICS-CONDENSED MATTER, 2004)
We report on first-principles calculations for multilayers of zinc-blende half-metallic ferromagnets CrAs and CrSb with III-V and II-VI semiconductors, in the {[}001] orientation. We examine the ideal and tetragonalized structures, as well as the case of an intermixed interface. We find that, as a rule, half-metallicity can be conserved throughout the heterostructures, provided that the character of the local coordination and bonding is not disturbed. We describe a mechanism operative at the interfaces with semiconductors that can also give a non-integer spin moment per interface transition atom, and derive a simple rule for evaluating it.